A NARRATIVE DISCOURSE OF A CROSS-CULTURAL STUDY EXPERIENCE IN A CHINESE UNIVERSITY (Revue d’Études Sino-Africaines, 2022)
In this paper, through a personal narrative discourse, I explore the influence and the contribution of my crosscultural study experience in China on my development as a young researcher. Through the Chinese academic culture, I learned some best practices that I consider essential for the blossoming and development of a student. Nonetheless, I also face some challenges such as language problems, communication with teachers, and even with classmates. Despite the issue of language and cultural disparities that were significant upon my arrival, I have managed to adapt and learn from Chinese society, teachers, and students. Also, the challenges that I had to overcome were not comparable to the knowledge acquired, and the rich experience that I have accumulated throughout the years spent in China. Through this personal narrative discourse, the different metaphors used to depict our academic life experience in China can enable the reader to have a kind of educative outlook.